The relationship of personality and executive functions in high-level soccer athletes: expertise-and gender-specific differences - Jan Spielmann; Jan Spielmann; Adam Beavan; Jan Mayer; Jan Mayer (Frontiers Media S.A., 2023)
BackgroundPsycho-cognitive factors such as personality and executive functions (EFs) are influential parameters when it comes to examining expertise in high-level soccer. Therefore, the profiles of those athletes are relevant both from a practical and scientific point of view. The aim of this study was to investigate the relationship between personality traits and executive functions with age group as an influential factor in high-level male and female soccer players.MethodsPersonality traits and executive functions of 138 high-level male and female soccer athletes from the U17-Pros teams were assessed using the big-five paradigm. A series of linear regressions investigated contributions of personality on EF assessments and team, respectively.ResultsLinear regression models showed both negative and positive relationships between various personality traits, executive function performance and the influence of expertise and gender. Together, a maximum of 23% (R2 = 6%-23%) of the variance between EFs with personality and various teams, demonstrating that many unaccounted-for variables remain at play.ConclusionThe results of this study demonstrate the inconsistent relationship between personality traits and executive functions. The study calls for more replication studies to help strengthen the understanding of relationships between psycho-cognitive factors in high-level team sport athletes.